DIS3L2 and LSm proteins are involved in the surveillance of Sm ring-deficient snRNAs - Roithová, Adriana; Feketová, Zuzana; Vaňáčová, Štěpánka; Staněk, David (Nucleic acids research, 2020)
Spliceosomal small nuclear ribonucleoprotein particles (snRNPs) undergo a complex maturation pathway containing multiple steps in the nucleus and in the cytoplasm. snRNP biogenesis is strictly proofread and several quality control checkpoints are placed along the pathway. Here, we analyzed the fate of small nuclear RNAs (snRNAs) that are unable to acquire a ring of Sm proteins. We showed that snRNAs lacking the Sm ring are unstable and accumulate in P-bodies in an LSm1-dependent manner. We further provide evidence that defective snRNAs without the Sm binding site are uridylated at the 3' end and associate with DIS3L2 3'→5' exoribonuclease and LSm proteins. Finally, inhibition of 5'→3' exoribonuclease XRN1 increases association of ΔSm snRNAs with DIS3L2, which indicates competition and compensation between these two degradation enzymes. Together, we provide evidence that defective snRNAs without the Sm ring are uridylated and degraded by alternative pathways involving either DIS3L2 or LSm proteins and XRN1.
Keywords: Protein Binding; sekvence nukleotidů; Nucleic Acid Conformation; vazebná místa; RNA Transport; RNA malá jaderná; RNA, Small Nuclear; exoribonukleasy; Exoribonucleases; stabilita RNA; Proto-Oncogene Proteins; SMN Complex Proteins; organely; HeLa buňky; vazba proteinů; Binding Sites; konformace nukleové kyseliny; Organelles; lidé; HeLa Cells; Humans; RNA-Binding Proteins; RNA Stability; transport RNA; protoonkogenní proteiny; Base Sequence; proteinový komplex SMN; proteiny vázající RNA